2023
DOI: 10.1021/acsanm.3c01529
|View full text |Cite
|
Sign up to set email alerts
|

An Ab Initio Study of Two Dimensional SnX2 and Janus SnXY (X = S, Se) Nanosheets as Potential Photocatalysts for Water Splitting

Abstract: Discriminating appropriate two-dimensional (2D) photocatalysts for hydrogen generation is among the most prospective schemes to tackle with environmental contaminations. Unfortunately, the inferior capability to harvest solar light together with fast recombination of photoexcited carriers can severely reduce the catalytic ability with consequent limited commercial applications. In this work, a series of single-layer MXY (M = Ge, Sn; X, Y = S, Se, and Te) containing T-and Hphases about photocatalytic capabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Table S2 summarizes the related detailed parameters and binding energy of excitons along with the indirect HSE06 band gaps. Moreover, the exciton binding energies of T-SnX 2 @SnSSe vdWHs (0.14–0.34 eV) are smaller than those of the corresponding isolated materials and TMD (0.51–0.62 eV) monolayers . The conclusion can confirm the dissociation of photoexcited carrier pairs during the redox reaction.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Table S2 summarizes the related detailed parameters and binding energy of excitons along with the indirect HSE06 band gaps. Moreover, the exciton binding energies of T-SnX 2 @SnSSe vdWHs (0.14–0.34 eV) are smaller than those of the corresponding isolated materials and TMD (0.51–0.62 eV) monolayers . The conclusion can confirm the dissociation of photoexcited carrier pairs during the redox reaction.…”
Section: Resultsmentioning
confidence: 62%
“…The corresponding freestanding materials based on HSE06 functionals are initially considered, as plotted in Figures S16–S17. Table S1 indicates that the band gaps of MX 2 and Janus MSSe monolayers based on the HSE06 functional are 0.48–2.37 eV for the T phase and 0–1.49 eV for the H phase, which are in good accordance with the previous research. The band gap of Janus MSSe is between those of MS 2 and MSe 2 regardless of the T or H phase, which is similar to the variation tendency of the lattice parameter. Nevertheless, the band gaps of both-phase MX 2 @MSSe vdWHs are all lower than those of their parent materials regardless of the PBE or HSE06 functionals (Figures and S18–S20), which is common in constructing vdW layered compounds.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, IV–VI chalcogenides MLs have emerged as a new class of 2D semiconductors that are nontoxic, chemically and experimentally stable, and abundant on earth . It has been reported that 2D SnXY (X, Y = S, Se) layers, including SnS 2 , SnSe 2 , and janus SnSSe, can be successfully synthesized using method like chemical vapor deposition (CVD). Numerous SnXY-based vdWHs with important applications have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Following that, a theoretical study has shown that SnS 2 nanosheet can be dynamically stable in both Tand H-phases [23]. Furthermore, a series of group IV dichalcogenide monolayers, MXY (M = Ge, Sn; X, Y = S, Se, and Te) containing T and H phases have been explored using first-principles calculations and proposed for photocatalytic water splitting applications [24]. It has also been reported that the PbS 2 monolayer exhibits an unusual negative Poisson's ratio and suitable band edge alignment, which makes it a promising catalyst for photocatalytic water splitting applications [25].…”
Section: Introductionmentioning
confidence: 99%